DUGAAN UJARAN PENGHINAAN DAN PENGANCAMAN DI MEDIA SOSIAL: KAJIAN LINGUISTIK FORENSIK - Alfetty, Cessara (University of Brawijaya, 2024)
This study analyzes the content of Facebook status comprising of the written status and its picture assumed to use insulting and threatening words toward Indonesian President Joko Widodo. This study uses a descriptive qualitative method by using Searle’s (1976) speech act theory as well as Kress and Leeuwen’s (2021) multimodality. The analyzes shows that there are 4 representative speech acts, 3 expressive speech acts, and two directives speech acts on the Facebook status. Moreover, this study also shows that the verbal element extends the visual element, providing additional information about the main object being discussed. The verbal mode is not dependent on the visual mode so the written status on the Facebook can be reported to the police as an offence warranting complaint based on the verbal mode only. However, the visual mode cannot be carried out to the authorities and reported as an offence warranting complaint because the visual mode has does not correspond with the verbal mode.